Synthesis and Antibacterial Study of Aspirin-Chalcone Derivatives - Zainab, Ngaini; Ho, Doris Ai Hui; Hasnain, Hussain; Wan Sharifatun Handayani, binti Wan Zullkiplee; Meng, Guan Tay; Norhasnan, Sahari; Norsyafikah Asyilla, Nordin (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The chemistry of aspirin and chalcone derivatives has been extensively studied and developed as one of the pharmaceutically important molecules. In this study, new aspirin-chalcone derivatives have been successfully synthesized and characterized via FTIR, 1H and 13C NMR spectroscopy. The antibacterial activities of synthesized compounds were investigated towards Escherichia coli ATCC 8739 via turbidimetric kinetic method. The newly synthesized aspirin-chalcone derivatives, however showed poor antibacterial activity against E. coli ATCC 8739 at the concentration of 50, 80 and 100 ppm. The effect of the molecular structure of the synthesized compounds on the antibacterial activity is discussed.